2018
DOI: 10.1063/1.5024380
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the effect of soft-core potentials and Coulombic potentials on bremsstrahlung during laser matter interaction

Abstract: An intense, short laser pulse incident on rare-gas clusters can produce nano-plasmas containing energetic electrons. As these electrons undergo scattering, from both phonons and ions, they emit bremsstrahlung radiation. Here, we compare a theory of bremsstrahlung emission appropriate for the interaction of intense lasers with matter using soft-core potentials and Coulombic potentials. A new scaling for the radiation cross-section and the radiated power via bremsstrahlung is derived for a soft-core potential (w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 43 publications
1
3
0
Order By: Relevance
“…the delayed (e -, 2e -) one contributes the most to TI. This is consistent with soft potentials not accurately describing scattering of a recolliding electron from the core [23].…”
Section: Details Of How We Accurately Account For the Coulomb Singula...supporting
confidence: 80%
See 2 more Smart Citations
“…the delayed (e -, 2e -) one contributes the most to TI. This is consistent with soft potentials not accurately describing scattering of a recolliding electron from the core [23].…”
Section: Details Of How We Accurately Account For the Coulomb Singula...supporting
confidence: 80%
“…However, softening the Coulomb potential fails to accurately describe electron scattering from the core [23,24]. Indeed, the ratio of the scattering amplitude for the softcore potential over the one for the Coulomb potential decreases exponentially with increasing momentum transfer [23,24]. For recollisions [25], this implies that soft potentials are quite inaccurate for high energy recolliding electrons that backscatter.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…that the potential-depth parameter has a large influence on the scattering cross section and thus the energy absorbed. However, it was found that the cross section saturates for large potential depths, but this value occurs at a potential depth that is typically larger than the ionization potential by an order of magnitude [22,29].…”
Section: Numerical Inverse Bremsstrahlung Heatingmentioning
confidence: 99%